Assessment of the Role of Kogi State Government in Flood Mitigation in Lokoja, Kogi State, Nigeria - Peter EDOKA (FUDMA Journal of Engineering and Technology, 2026)
Flooding due to overwater flow of both natural and human-made causes is a perennial environmental problem in the world and in Nigeria. Kogi State is especially prone to Lokoja, the state capital, which is characterised by the confluence of both the Niger and Benue rivers, the rapid urbanisation process, the insufficient drainage facilities, and climate diversity. Although repetitive floods have led to massive destruction of homes, farmland, infrastructures, and livelihoods, few studies have been done to measure mitigation measures at the state level. This paper tries to fill this gap by evaluating the contribution of the Kogi State Government to curbing floods in Lokoja. The objectives included finding key causes of flooding, studying socio-economic effects, assessing structural and non-structural mitigation strategies, and developing strategies to better manage floods. The descriptive survey design was taken up, and both primary and secondary data were utilised. Formed questionnaires were distributed to 400 residents of flood-prone communities, and field observations and examination of governmental documents were also utilised. The analyses of data were performed with the help of descriptive statistics, frequency counts, percentages, and the Relative Importance Index. The results show that flooding is mainly caused by heavy rain, lack of drainage and overflow of rivers, which is aggravated by the blocked drains and uncontrolled construction. Although structural interventions like drainage systems and embankments are available, and non-structural measures, including awareness campaigns and early warning systems, are partially in place, such measures are only slightly effective. The research paper has concluded that more infrastructure, better control implementation, more efficient warning systems, and better inter-agency coordination are required to mitigate the risk of floods and safeguard exposed communities at Lokoja.